Existence of Solutions of Second Order Boundary Value Problems with Integral Boundary Conditions and Singularities. (12th May 2010) - Ye, Guoju; Li, Xiuli
Abstract : By the notation and monotone convergence theorem of Henstock-Kurzweil integral, we investigate the existence of continuous solutions for the second order boundary value problems with integral boundary conditions in which the nonlinearitiesf ( t, x ( t ) ) are allowed to have the singularities in t and are not Lebesgue integrable.